Pengaruh Waktu Inkubasi Terhadap Biokonversi Reject Nanas Menjadi Bioetanol - M Ridwan Afitra; Adrianto Ahmad; Chairul Chairul (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
Bioethanol can be produced through a fermentation process materials containing starch, sugar and cellulose fibers by fermentation by microorganisms. Bioethanol can be used as solvents, materials manufacture of perfumes, flavorings, food coloring, and drugs, and even can be used as an alternative fuel. Bioethanol production is done by a process bacth or also called bulk process. The purpose of this study was to determine the effect of incubation time and also get the optimum concentration of ethanol in the manufacture of bioethanol from pineapple reject. Stages of the manufacturing process starts from the substrate pineapple reject juice. Effect of incubation time will be done in this study with variations of 24, 48, 72, 96 and 120 hours. The number of cells during the incubation period will be analyzed by measuring the dry weight of the cell. Fermentation will take place over 4 days (96 hours) with a variation of 12, 24, 36, 48, 60, 72, 84 and 96 hours with the help of Saccharomyces cerevisiae. The results showed that the best time of incubation occurred at 24 and 48 hours with each cell weight of 9.8 g/L and 10.1 g/L at 96 hours of fermentation time and 48 hours which produces bioethanol concentration of 7%.Keywords : bioethanol, fermentation, incubation, pineapple reject, saccharomyces cerevisiae